What Drives Consumer’s Intention to use Online Property Websites: A Conceptual Model - Mui, Dyana Ling Chang; Rizal Hamid; Nelson Lajuni; Norazah Mohd Suki (2018)
The real estate market in Malaysia is growing as the nation grows more prosperous. There were 376,583 transactions recorded in Malaysia in 2010 with an aggregate worth RM107.44 billion (Construction Industry Development ,2016). This study intends to inspect the factors that drive consumer’s intention to use online property website. Previous literature does not include in-depth analyses such as consumer behavior. Hence, this conceptual paper proposes a model the key constructs that determine consumers‟ intention to use online property website based on the Stimulus-Organism-Response (S-O-R) model. The proposed model integrates the S-O-R model with atmospheric cues from websites such as informativeness, effectiveness and entertainment. The results of the study provide significant insights the phenomenon of using online property ads and factors that influence consumers‟ intention regarding online property websites. Recommendations for future research are also presented.